Terbentuknya Daerah Penangkapan Ikan dengan Light Fishing - Rita L Bubun; Domu Simbolon; Tri Wiji Nurani; Suro Hari Wisudo (Jurnal Airaha, 2015)
This study aims to formulate the formation procces fishing ground in the fisheries light fishing. The method used in this research is survey method. The research object have been using the catch in purse seine and “bagan apung” units. Data analysis have been using descriptive quantitative analysis and trophic level analysis. The result showed that formulation of the formation fishing ground by light fishing are : (1) interaction physical between species by light fishing create the composition are Stolephorus sp, Euthynnus affinis, Sardinella gibbosa, Scomberoides commersonnianus, Caranx sexfasciatus, Carangoides praeustus, Sphyraena jello, Leptojulis cyanopleura, Parastromateus niger, Penaeus indicus, and Loligo sp; (2) the interaction biology between one species with other species create the composition are Katsuwonus pelamis, Sardinella lemuru, Selar crumenophthalmus, Selaroides leptolepis, Decapterus macrosoma, Rastrelliger kanagurta, Thunnus albacares and Coryphaena hippurus.